EDUCATIONAL TRAINING SIMULATOR FOR MONITORING READING TECHNIQUE AND SPEED BASED ON SPEECH-TO-TEXT (STT) METHODS - Olesia Barkovska; Heorhii Ivashchenko; Dmytro Rosinskiy; Daniil Zakharov (Інформаційні технології і засоби навчання)
The work is devoted to a relevant issue – gamification of the educational process of primary school students with the use of digital mobile devices using the example of educational trainer developed to control the technique and speed of reading. The practical novelty of the study lies in its potential to optimize the process of controlling reading techniques for children with various speech disorders, such as lisping, rhotacismus, and dyslalia, which remains an unsolved problem for existing computer linguistic models. The practical significance lies in the fact that the use of information and communication technologies and gamification of the learning process motivates to gain knowledge and encourages learning not only due to the game strategy, but also due to the fact that the child receives approval and the opportunity to perform the task again so to improve skills. The proposed and tested trainer for monitoring the technique and speed of reading of primary school students for a mobile digital device recognizes the child’s voice with high accuracy (up to 94.84%), detects misread words and counts the number of words read in the given time period. The architecture of the proposed system consists of the following modules: preparation module, which ensures the correct functioning of the system regardless of the existing speech disorders; the speech-to-text converter directly converts the voice of the child reading the text on the gadget screen into text; The text comparison module is responsible for comparing the text read aloud with the text obtained as a result of conversion. The results of testing children with lisping and rhotacismus problems showed that the Jaro algorithm has a slightly higher accuracy of comparing two texts (by an average of 1.14%), and, at the same time, a shorter comparison time for large text arrays (by 39%). The results of testing children with dyslalia, meaning the rearrangement of sounds in words when reading, also showed that the Jaro algorithm has a shorter line comparison time for large text arrays (by 7%). The reduced operation time in methods for comparing texts in dyslalia cases is attributed to the absence of text array variations, with evaluations solely focusing on potential permutations of sounds.